An interview with Daniel L. Smail - Riccardo Rao; Daniel L. Smail (Reti Medievali Rivista)
The interview with Daniel L. Smail traces his academic background and scholarly work as a medievalist, from Imaginary Cartographies (now translated into Italian as Cartografie immaginarie) to his recent projects on late medieval household inventories and documentary archaeology.